Modification Of Kaolin Capkala With Benzalkonium Chloride (Bkc) Surfactant And Antibacterial Activity Test Against Escherichia Coli - Jeny Clarita; Puji Ardiningsih; Nelly Wahyuni (JURNAL KIMIA MULAWARMAN, 2023)
A study was conducted to determine the antibacterial activity of modified benzalkonium chloride (BKC) kaolin Capkala against Escherichia coli (E. coli) bacteria. Kaolin modification begins by melting kaolin with sodium hydroxide (NaOH) and reacting using a reflux device. Furthermore, the sample was reacted with BKC at a concentration variation of 0, 2.5×10-3; 5×10-3, and 2.5×10-2 M for 6 hours with a stirring speed of 150 rpm. The modified kaolin was characterized using Fourier Transformed Infrared (FTIR), and adsorption tests were performed on Cl-. The FTIR spectrum of the modified kaolin showed an absorption peak at 2926.19 cm-1 C-H symmetrical from CH2, which indicated the attachment of surfactant to the kaolin. BKC modified kaolin antibacterial activity test using the halo test method. The adsorption test on Cl- and the antibacterial activity test on kaolin and modified kaolin increased with increasing BKC concentration, namely 3545; 3828.6, 3970.4; 4183.1 mg/L and the inhibitory diameter were 2.1±0.14, 3.3±0.14, 4.5±0.14, and 6±0.14 mm, respectively. The results showed that BKC can increase the antibacterial activity of kaolin